Consumo de sustancias inhalantes por los estudiantes de la unidad educativa Martha Bucaram de Roldos sección nocturna de la ciudad de Yantzaza, año 2015. - Calva Chuquimarca, Carmen Noemí (2015)
This research called consumption of inhalants among students in the night section of the Education Unit Martha Roldos Bucaram city Yantzaza. 2015, aims to determine the prevalence of substance use. The methodological design used in the study was explanatory, descriptive, retrospective, analytical, cross, field and bibliographic. To effect the technique of direct observation and survey instrument was applied with the observation guide and questionnaire, using sample to 50 students with addiction problems, where the factors that lead to the consumption of inhalants are identified as: family with 21.27%, with 35.86% Social and personal with 42.85%, compared to the results exposed the author was raised implement an action plan in order to make young students aware of the consequences it produces inhalant use substances in the body based on educational activities such as training and projection of audio video designed to reduce consumption and to reinforce knowledge the leaflets delivery and leaflets which were handed to all participants performed the delivery was made an educational banner vocational guidance department for more information to students, then proceeded to provide psychological care in order to improve the physical and emotional state of young people. Finally open in the central park of Yantzaza and educational institutions were invited to participate in the development of the house was done